Tumor-infiltrating regulatory T cell: A promising therapeutic target in tumor microenvironment - Tianning Huang; Fan Li; Yiming Wang; Jian Gu; Ling Lu; Peifang Wei (Chinese Medical Journal)
Abstract. Regulatory T cell (Tregs) predominantly maintain the immune balance and prevent autoimmunity via their immunosuppressive functions. However, tumor-infiltrating Tregs (TI-Tregs) may mediate tumor immune tolerance in complex tumor microenvironments, resulting in poor prognosis. Distinguishing specific TI-Treg subpopulations from peripheral Tregs and intratumoral conventional T cells (Tconvs) has recently emerged as an important topic in antitumor therapy. In this review, we summarize novel therapeutic approaches targeting both the metabolic pathways and hallmarks of TI-Tregs in preclinical and clinical studies. Although the phenotypic and functional diversity of TI-Tregs remains unclear, our review provides new insights into TI-Treg-based therapies and facilitates precision medicine for tumor treatment.